A NaV3(PO4)3@C hierarchical nanofiber in high alignment: exploring a novel high-performance anode for aqueous rechargeable sodium batteries. Issue 12 (13th March 2017) - Ke, Linlin; Dong, Jing; Lin, Bo; Yu, Tiantian; Wang, Huifeng; Zhang, Sen; Deng, Chao
Abstract : A well-aligned NaV3 (PO4 )3 @C nanofiber with a hierarchical architecture and fast sodium intercalation capability is a novel high property anode for aqueous rechargeable sodium ion batteries. Abstract : The development of aqueous rechargeable sodium batteries (ARSBs) demands high-performance electrode materials, especially anode materials with low operating potential and competent electrochemical properties. The lithium/sodium vanadium phosphate family with good structural stability and abundant vanadium chemistry versatility is a promising series for energy storage applications. Herein, a new member in the sodium vanadium phosphate family, i.e. NaV3 (PO4 )3, is introduced as a novel anode candidate for ARSBs. For the first time, its sodium intercalation mechanism in an aqueous electrolyte is explored, and moreover, the well-aligned NaV3 (PO4 )3 @porous carbon nanofiber is constructed to fulfil its full potential. Based on the reversible phase transformation and 3D open framework, the NaV3 (PO4 )3 is demonstrated to be reliable in the aqueous electrolyte. Favored by the well-aligned, highly porous and hierarchical 1D nanoarchitecture, the freestanding aligned NaV3 (PO4 )3 @porous carbon hybrid film achieves fast electron/ion transport capability and good mechanical flexibility, resulting in its superior high-rate properties and excellent cycling durability. Moreover, a full cell is fabricated using the aligned NaV3 (PO4 )3 @C nanofiber as the anode and Na0.44 MnO2 as the cathode. The cell is capable of high-rate long-term cycling, which retains 84% of the capacity after five hundred cycles at alternate 20 and 5C. Therefore, this work not only demonstrates a novel high-performance anode material for ARSBs, but also introduces a general applicable and highly efficient architecture of aligned 1D nanofibers for energy storage applications.